Intelligent Systems Supporting the Use of Energy Systems and Other Complex Technical Objects, Modeling, Testing and Analysis of Their Reliability in the Operation Process - Duer, Stanisław (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book focuses on a novel application of Intelligent Systems for supporting the operation and maintenance of power systems or other technical facilities within wind farms. Indicating a different perception of the reliability of wind farm facilities led to the possibility of extending the operation lifetime and operational readiness of wind farm equipment. Additionally, the presented approach provides a basis for extending its application to the testing and analysis of other technical facilities.